Pengaruh Flexible Work Arrangements Terhadap Employee Retention Dengan Work-Life Balance Sebagai Variabel Mediasi Pada Karyawan Gen-Z di Indonesia - Reinhart Mathew Rodotua; Anike Retawati; Aprilita Aprilita; Indah Nur Oktavia (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
The purpose of this study is to examine how flexible work arrangements (FWA) affect employee retention among Indonesian Generation Z workers, using work-life balance (WLB) as a mediating variable. The high turnover rate among Generation Z, who value freedom but are prone to suffering an imbalance between their personal and professional life, serves as the study's backdrop. 140 Generation Z employees of a startup company were given questionnaires to complete as part of this study's associative quantitative method. Using SmartPLS 3.0 software, the Partial Least Square-based Structural Equation Modeling (SEM-PLS) method was used to analyze the data. The findings demonstrated that employee retention was positively and significantly impacted by flexible work options. Additionally, as work-life balance had a positive and large impact on employee retention, FWA also had a favorable and significant impact on work-life balance. The study's primary conclusion is that the association between flexible work schedules and employee retention is partially mediated by work-life balance. The study's conclusions suggest that in order to successfully retain Generation Z talent, organizations must support work-life balance and embrace flexible work practices.